First results of the “Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS)” - Jakob, Carolin Ellen Marianne; Borgmann, Stefan; Duygu, Fazilet; Behrends, Uta; Hower, Martin; Merle, Uta; Friedrichs, Anette; Tometten, Lukas; Hanses, Frank; Jung, Norma; Rieg, Siegbert; Wille, Kai; et al. (Infection, 2021)
Knowledge regarding patients’ clinical condition at severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection is sparse. Data in the international, multicenter Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) cohort study may enhance the understanding of COVID-19.